FENOMENA POLITIK IDENTITAS DALAM KACAMATA KRITIS MULTIKULTURALISME DI INDONESIA - Muhammad Padjar Gemilang (UNIVERSITAS SERAMBI MEKKAH, 2024)
The phenomenon of identity politics which opposes the unity and integrity of Indonesian society is a form of denying the struggle for recognition of the diversity that exists in Indonesia. National unity and peace have been eroded due to identity political movements led by certain groups. Religion, ethnicity and gender are examples of identity politics that can complicate democracy. One of the positive aspects of identity politics is its potential to increase the political voice and involvement of underrepresented groups. However, this has the potential to increase political polarization and trigger conflict between factions. Identity politics has the potential to further divide society, cloud political discourse, and even inspire bigotry and prejudice. But identity politics, when used correctly, can also be a tool for democratizing social inclusion. The aim of writing this article is to analyze and criticize identity politics in multiculturalism theory. This theory explains the ways in which certain groups exploit identity politics to strengthen their authority, either by highlighting their own identities or erasing the identities of other groups. This research uses a library research strategy based on book analysis. The results obtained are how this theory criticizes the identity politics approach which limits the space for public discussion by focusing only on certain identities, thereby ignoring other issues, as well as excessive identity politics which can result in justice segmentation between various groups.